2022
DOI: 10.1038/s41593-022-01171-w
|View full text |Cite
|
Sign up to set email alerts
|

Thalamus-driven functional populations in frontal cortex support decision-making

Abstract: Neurons in frontal cortex exhibit diverse selectivity representing sensory, motor and cognitive variables during decision-making. The neural circuit basis for this complex selectivity remains unclear. We examined activity mediating a tactile decision in mouse anterior lateral motor cortex in relation to the underlying circuits. Contrary to the notion of randomly mixed selectivity, an analysis of 20,000 neurons revealed organized activity coding behavior. Individual neurons exhibited prototypical response profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 67 publications
(169 reference statements)
6
33
0
Order By: Relevance
“…8B). Altogether, these observations indicate that functional properties of neurons are tighly linked to their long-range projections – a pattern that strongly resonates with recent experimental findings [13, 71]. Constraining model architectures with connectomics, and then using models to interpret neural recordings, represents a promising line of future research.…”
Section: Discussionsupporting
confidence: 76%
“…8B). Altogether, these observations indicate that functional properties of neurons are tighly linked to their long-range projections – a pattern that strongly resonates with recent experimental findings [13, 71]. Constraining model architectures with connectomics, and then using models to interpret neural recordings, represents a promising line of future research.…”
Section: Discussionsupporting
confidence: 76%
“…Hirokawa et al 13 further linked a group of functionally distinct neurons to a specific projection target, suggesting that functional separation might be accompanied by distinct connectivity. In mouse anterior lateral motor cortex (ALM), functional subpopulations were also found and linked to the varying strength of input from other brain areas 15 . A study in MEC specifically investigated selectivity for time and space of individual neurons across visually different environments 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Individual neurons in PFC have in general been found to encode not a single variable, such as a particular stimulus or feature, but instead are often selective for multiple variables ("mixed selectivity") 11 and modulate their firing preference to changing circumstances, contexts, or rules 12 . On the other hand, recent experimental work has shown that neurons in many areas are specialized for processing specific kinds of information [13][14][15] , and theoretical work has explored the benefits and conditions under which functional specialization might arise 16,17 . However, so far, in the medial prefrontal cortex (mPFC), evidence for functional specialization, including biases in mixed selectivity, is scant.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the neural circuits underlying basic phenomena of motor planning (i.e. spatial memory and movement initiation in 2AFC tasks), have been revealed in rodents models (Bharmauria et al, 2020, Duan et al, 2021, Guo et al, 2017, Inagaki et al, 2019, Li et al, 2016, Yang, 2022. Our behavioral paradigm and neurophysiological observations provide a basis for employing the latest tools of rodent systems neuroscience to make progress in understanding all the phenomena associated with ethological motor planning.…”
Section: /43mentioning
confidence: 99%